Murder in time : a novel - McElwain, Julie (McElwain, Julie. Kendra Donovan series., 2016)
Beautiful and brilliant, Kendra Donovan is a rising star at the FBI. Yet her path to professional success hits a speed bump during a disastrous raid where half her team is murdered, a mole in the FBI is uncovered and she herself is severely wounded. As soon as she recovers, she goes rogue and travels to England to assassinate the man responsible for the deaths of her teammates. While fleeing from an unexpected assassin herself, Kendra escapes into a stairwell that promises sanctuary but when she stumbles out again, she is in the same place - Aldrich Castle - but in a different time: 1815, to be exact. Mistaken for a lady's maid hired to help with weekend guests, Kendra is forced to quickly adapt to the time period until she can figure out how she got there; and, more importantly, how to get back home. However, after the body of a young girl is found on the extensive grounds of the county estate, she starts to feel there's some purpose to her bizarre circumstances. Stripped of her twenty-first century tools, Kendra must use her wits alone in order to unmask a cunning madman. ~Book jacket.